Species‐specific schooling behaviour of fish in the freshwater pelagic habitat: an observational study. Issue 1 (6th April 2020) - Holubová, Michaela; Blabolil, Petr; Čech, Martin; Vašek, Mojmír; Peterka, Jiří
Abstract: Social living of animals is a broadly occurring phenomenon, although poorly studied in freshwater systems, fish schooling behaviour is an excellent example. The composition of fish schools, species‐specific schooling tendencies and preferences of adult fish were studied in the pelagic habitat of the Římov Reservoir, Czech Republic. Video recordings captured over a total of 34 days (16 h per day) in the clear water period of three seasons were analysed. From four species identified as school‐forming species – bream, bleak, roach and perch, 40% of the individuals observed formed schools of 3–36 individuals. Although conspecific schools prevailed, 20% of individuals formed heterospecific schools, except bleak that schooled strictly with conspecifics. Schools were composed of individuals of similar body size and life strategy. Heterospecific schools were significantly larger than conspecific schools and showed uneven proportion among species, that is, one species being more abundant when the school dimension increased. Probability of encounter in bleak was lowest and proved highest inclination for schooling. Gregarianism levels depended on species morphology and body size, with larger and morphologically advanced fish tending less to sociability. This indicates that the antipredator function of schooling behaviour is intensified with increasing vulnerability of the species.